Evaluation of government sector blood banking system of a rural area of West Bengal, India - Ayan Chakraborty; Pallabi Dasgupta (Journal of Clinical and Scientific Research)
Background: Blood transfusion service (BTS) is a vital part of health care services. Studies have documented various problems faced by the Indian BTS. A comprehensive assessment blood banking system will serve as a baseline for improvement to be implemented at the district level. The study was done to assess the blood banking system of Purba Medinipur district, West Bengal, India. Methods: A descriptive cross-sectional study was conducted in six government blood banks of Purba Medinipur. A structured checklist for the assessment of blood banks was developed based on National Blood Transfusion Council (NBTC) guidelines of India and given weighted scores in various domains such as licensing, annual collection, blood donation, Technical Immuno-haematology (TECH-IH), TECH transfusion-transmitted infections (TECH-TTIs), quality management system (QMS) and general. Results: All the blood banks were having valid licenses. The obtained mean score of the district was 81.8 ± 6.7. Contai Blood Bank obtained the highest (92%) score, followed by Haldia (88%) and Tamluk (83%). Domain-wise mean scores of the district in the annual collection were 4.1 ± 1.4 (82%), blood donation domain 10.7 ± 0.8 (97.3%), TECH-IH 15.2 ± 1.6 (84.4%), TECH-TTI 17 ± 3.3 (85%), QMS 25.5 ± 3.3 (72.9%) and general category 6.5 ± 0.8 (81.3%). Overall TTI detection status of the district was 0.59%. Conclusions: Overall performance of the high-burden blood banks was satisfactory. Mostly, compliance with NBTC guidelines, availability of standard operating procedures for technical processes, etc., are in the proper place. However, inadequate human resources can be a basic and real problem for proper implementation. Proper accreditation might improve the services in all the areas of BTS.